EXPLORATION OF FACTORS AFFECTING AUDIT QUALITY (EMPIRICAL STUDY AT ONE OF THE PUBLIC ACCOUNTING FIRMS IN SURABAYA) - Syahda, Keisya Anindya; Islamudin, Ardhi; Vizandra, Ellyzabeth Putri; Fitriani, Nurul (JEA17: Jurnal Ekonomi Akuntansi, 2025)
This study aimed to explore how auditors at a medium-sized Public Accounting Firm (KAP) in Surabaya understood and responded to various factors influencing audit quality, including time pressure, team dynamics, ethical challenges, and institutional demands. A descriptive qualitative approach with a case study design was applied. Data were collected through semi-structured interviews with two senior auditors, participatory observation, and documentation. Thematic analysis was carried out using structured pattern identification and triangulation of techniques and sources to ensure credibility. The findings reveal seven key themes: understanding audit quality, audit quality indicators, auditor experience, professionalism under pressure, time management strategies, team communication culture, and maintaining audit integrity under institutional pressure. The study shows that audit quality is shaped by procedural compliance, professional ethics, effective teamwork, and adaptive strategies. Experience and professionalism play a critical role in managing pressure and maintaining objectivity. This research contributes to understanding the behavioural dynamics of auditors and highlights the importance of synergy between ethics, competence, and collaboration in the Indonesian audit context. Keywords: audit quality, professionalism, team dynamics, institutional pressure, qualitative study